Only in the heat of the moment? A study of the relationship between weather and mortality in Germany - Martin Karlsson; Maike Schmitt (Technische Universität Darmstadt, Department of Law and Economics, 2011)
In this study we analyze the relationship between heat events and mortality in Germany. The main research questions are: Does heat lead to rising mortality and if yes, are the effects persistent or compensated for in the near future? Furthermore, we consider differences between heat effects in urban and rural environments. Cause specific daily mortality and meteorological data is connected on the county level. We allow for static as well as dynamic relations between extreme temperatures and mortality and implement several panel data estimation approaches. We find that heat has a significant positive impact on mortality. The strongest effects can be measured on the day when heat occurs and the first week afterwards. The mortality increase ranges between 0.003 and 3.5 per 100,000 inhabitants depending on the particular death cause. We do not find a significant negative, and thus compensating impact in a medium term, which is in the contrary to the Harvesting Hypothesis. Using a value of statistical life approach we estimate that one additional hot day in Germany induces for the overall population a loss of m 1,861. Moreover, the environment plays an important role. The heat induced increase in mortality is significantly higher in urban areas.
Keywords: 330; Climate Change; Harvesting Hypothesis; Heat Waves; Mortality; Urban Heat Island effect; Wetter; Klimawandel; Sterblichkeit; Wert des Lebens; Schätzung; Deutschland